2009
DOI: 10.1097/ico.0b013e31818c4d62
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Thickness in a Population-Based, Cross-Sectional Study: The Tehran Eye Study

Abstract: The mean CCT in the present study was 555.6 microm, which is relatively higher in comparison with that in other ethnic groups. In the multiple regression model, age and ACD were correlated with the CCT, but refractive errors showed no correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
45
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 38 publications
13
45
5
Order By: Relevance
“…Central corneal thickness can also affect variations in corneal biomechanical indices; most East Asian populations have thinner corneas than European and Iranian populations. 21 In our study, girls had a higher CRF than boys; this was true even after adjusting for CCT. However, we did not find a statistically significant difference in CH between boys and girls.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Central corneal thickness can also affect variations in corneal biomechanical indices; most East Asian populations have thinner corneas than European and Iranian populations. 21 In our study, girls had a higher CRF than boys; this was true even after adjusting for CCT. However, we did not find a statistically significant difference in CH between boys and girls.…”
Section: Discussionmentioning
confidence: 65%
“…Similar studies give a detailed description of these indices in different populations. [13][14][15][16][17][18][19][20][21][22][23][24] Results in our study showed that the mean CRF was 11.74 mm Hg and its normal range was from 8.19 to 15.28 mm Hg. The mean CH in this study was 11.49 mm Hg with a normal range from 7.67 to 15.31 mm Hg.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies with a more biased study population also found weak but statistically significant correlation between corneal thickness and age and the increase in CCT throughout life. 13,15 Using CCT as a basis, 2 large population studies in Asia did not find significant differences between CCT and refractive state or keratometry. 15,16 They did, however, report an increased CCT in men compared with women.…”
Section: Discussionmentioning
confidence: 98%
“…Gray sectors Sectors where there was no significant difference in regional thickness between age groups, white sectors sectors where there was a significant difference between the age groups. *, **Significantly different at P \ 0.01 and P \ 0.001, respectively, according to the one-way analysis of variance test with age [17,[22][23][24][25]. Reinstein and colleagues reported that the CET is correlated with neither age nor spherical equivalent refraction [1].…”
Section: Discussionmentioning
confidence: 99%
“…Many demographic, ethnic, and ophthalmologic factors have been reported to be correlated with corneal thickness [17,19,[22][23][24][25], and these factors could also influence the CET. Some authors have reported that the central corneal thickness is not correlated with age [14,26], while others have indicated that the central cornea thins Fig.…”
Section: Discussionmentioning
confidence: 99%